Competencies of Court Experts for Road Traffic Accidents and Capacity of States to Perform Needed Expertise - Nešić, Miladin M; Bjelovuk, Ivana; Kesić, Tanja (NBP. Nauka, bezbednosti, policija, 2024)
Court expert plays important role in the road traffic accident expertise. The question is how to select an appropriate court expert and what guarantees the quality of expertise. A road traffic accident expertise requires expert competencies and a comprehensive court expert register. The analysis of expert competencies in the road traffic area is performed by surveying available data from the register of Serbia, Montenegro, Bosnia and Herzegovina, and North Macedonia (nonEU states) and Croatia and Slovenia (the EU states). A comparative review of legal solutions in the observed states was done in order to consider the legal bases for expertise. Proposal for improvement is made. The capacity indicators of states for performing expertise were defined and an analysis was carried out showing the highest load was on the Slovenian experts (1 day per expertise), while in Bosnia and Herzegovina - District of Brčko the indicator amounted to 34 days per expertise.